Analisis hubungan antara kualitas layanan jaringan dan pengalaman pengguna pada layanan video streaming youtube - Auliya, Kharisma Xena; Dian W. Chandra (Fakultas Teknologi Informasi, Universitas Kristen Satya Wacana, 2025)
The quality of user experience (Quality of Experience/QoE) in YouTube video streaming services is highly influenced by the quality of network service (Quality of Service/QoS). QoS measurement is conducted using Wireshark software with parameters such as throughput, packet loss, delay, and jitter, and assessed based on the TIPHON standard. Meanwhile, QoE is evaluated through a survey of 30 respondents and measured using the Likert scale.The analysis results indicate that QoS falls into the